Water management in agriculture : ten years of World Bank assistance, 1994-2004. - Pitman, George Keith, 1945- (Independent evaluation studies., 2007)
The need to promote increased trade, prevent the spread of HIV/AIDS, and ensure adequate water resources are some of the development challenges generating interest in increased regional and sub-regional cooperation. This evaluation seeks to provide guidance on when it is desirable for the Bank to support activities on a regional level, and assesses the effectiveness of both regional programs and the Bank's role in supporting them. It comes at a time of increasing interest in regional development programs, supported by recent theoretical work on regional public goods and regional trading arrang.